If cosecA+ cotA= p then cosecA- cotA= ?
Please answer this question.
Pleaseeeeeeeeeeeeeeeeeeeeeeeee......
With explanation.
Answers
Answered by
1
I hope it will help you........
Attachments:
![](https://hi-static.z-dn.net/files/dd6/dc9d62b9a0a9a6ea34a32d42647308a7.jpg)
Answered by
1
Step-by-step explanation:
Given that cosec A+cot A=p
The trigonometric identity
coesc² A-cot² A=1
=> (cosecA+cot A)(coesc A-cot A)=1
=> p(cosec A-cot A)=1
=> cosec A-cot A=1/p.
hope you got it and it is helpful to you.
Similar questions